Emergent management of severe post-TIPS bleed in patient with end-stage liver disease and coronary artery disease - Mohammad Arammash; Barbara Hamilton; Charles Rickert (Transplantation Reports)
Liver transplantation has become widely available but remains a high-risk operation not suitable in the presence of severe comorbidities. Pre-operative planning to address potential challenges is key to ensuring optimal outcomes. In this report, we highlight a challenging clinical situation in which a patient with severe portal vein thrombosis and coronary artery disease developed a significant bleed post TIPS, necessitating emergent ligation of the portal structures and urgent liver transplantation. The patient successfully underwent coronary artery bypass grafting after liver transplantation. This case demonstrates an unconventional method for remediating inaccessible portal vein hemorrhage secondary to transjugular intrahepatic portosystemic shunting and the ability to perform coronary artery bypass grafting post-liver transplantation.